Cinema, camera and action: Using a film to teach Biology topics in high school (Research, Society and Development, 2021)
Nowadays, more than ever, the teacher is challenged in proposing teaching methodological alternatives in order to awaken and facilitate students' learning. Biology is a fascinating area, however, it is endowed with many terms and processes that must be very well contextualized by the students. In this sense, the present work has as main objective the proposal of a didactic sequence to the students of the third year of high school, using the commercial film called “Victor Frankenstein” to facilitate the students' learning on themes related to the origin of life, and even even ethics and bioethics in scientific research. As an initial methodology, the film will be reproduced to the students and at the end, the teacher will discuss and discuss various subjects within the scope of Biology, enhancing and facilitating the knowledge acquired in the theoretical classes of Biology. Thus, we believe that the approach of the proposed film may arouse the interest of students, making learning more effective in the topics covered.